Evaluation of polycyclic aromatic hydrocarbons in cattle farms and its relation with the safety in grass and milk - Sosa, Dayana; Peña, Brizeidi; Escobar, A. C. (Cuban Journal of Agricultural Science, 2018)
In this study the concentration of polycyclic aromatic hydrocarbons (PAHs) in grass and milk was quantified, and the relation between their concentration in these matrices and those reported in the soil was estimated. A total of 15 grass sites were selected and of these, ten were milk producers. For this, the proximity to the emission sources and the concentrations of these pollutants in agricultural soils from Havana and Mayabeque were taken into account. Gas chromatography with mass detection was used for its identification and quantification. The results were analyzed by linear regression, descriptive statistics and simple ANOVA and Tukey test to determine differences in the studied matrices. The Infostat statistical package was used for this. The median concentration of the sum of the PAHs in grass and milk were 45.0 and 10.1 μg/kg, respectively, with predominance of phenanthrene. Significant associations were found between the PAHs concentrations between grass and soil (y = 2.4109x -11.073, R² = 0.8444, SE = 0.42, P <0.01), as well as in grasses and milk near sources of contamination (and = 0.1848x- 17.675, SE = 3.9E-03, R2 = 0.9996, P <0.05). The data presented contributes to the limited information on the presence of this group of persistent organic pollutants in cattle farms from the Caribbean region and it is concluded that the milk is safe, according to the European Union regulation and the grasses are of low risk for the animals health. Key words: pollution, CGMS, Cuba, livestock